Cisplatin-Induced Anorexia and Pica Behavior in Rats Enhanced by Chronic Stress Pretreatment - Guo, Zhijun; Duan, Jingjing; Chen, Yitian; Cai, Weijia; Yang, Chenghua; Yang, Zhen; Liu, Xiufeng; Xu, Feng (Frontiers in Pharmacology, 2022)
Background: Chemotherapy-induced nausea and vomiting severely impairs the treatment and prognosis of cancer patients. Depressive mood disorder might aggravate nausea and vomiting in cancer patients; however, the role of neurotransmitters and receptors involved in the mediation of emesis and nausea is still not well elaborated. Methods: The study was carried out based on the chronic unpredictable mild stress–induced depression-like phenotype rat model and cisplatin-induced pica rat model establishment. Forty male Sprague–Dawley rats were randomized into the non-treated control group and the chronic stress group, which were exposed to 8 weeks of stress. Each group was then sub-divided into vehicle subgroups (n = 10) and cisplatin subgroups (n = 10) which were given cisplatin to induce pica behavior. Kaolin and food intake were recorded after administration. The medulla oblongata and ileum tissues were obtained. Neurotransmitters involved in the mediation of emesis and nausea (5-HT, DA, SP, and AEA) were detected using an ELISA kit. Vomit-related receptors (5-HT3R, DA2R, NK1R, and CB1R) in tissues were assayed for mRNA and protein expression by RT-qPCR and Western blotting. Results: Behavioral test and sucrose preference validated that depression-like phenotype rat models were established successfully. The kaolin consumption test confirmed that chronic stress pretreatment aggravated anorexia and pica behavior. Vomiting-related molecules’ data showed that chronic stress exposure increased 5-HT and SP levels in the medulla oblongata. Vomiting-related receptor expression data showed that chronic stress pretreatment upregulated 5-HT3R, DA2R, and NK1R expressions and downregulated the CB1R expression in the medulla oblongata. However, chronic stress pretreatment downregulated 5-HT3R, DA2R, and NK1R expressions and upregulated the CB1R expression in the ileum. Conclusion: Chronic stress pretreatment aggravates anorexia and vomiting progress, which might be via altering neurotransmitters and receptors involved in the mediation of emesis and the nausea level and expression in the central nervous system.